Effect of milling speed and time on electrical properties and microstructure of SnO2-Co3O4-Dy2O3-Ta2O5 varistors. Issue 18 (15th December 2018) - Miranda-López, Martin I.; Hernández, M.B.; Zambrano-Robledo, Patricia; García-Ortiz, L.; García-Villarreal, S.; Rodríguez, C. Gómez; Aguilar-Martínez, J.A.
Abstract: Ceramic sintered pellets with chemical composition 98.9%SnO2 –1%Co3 O4 –0.05%Dy2 O3 –0.05%Ta2 O5 were prepared by mixing raw materials in a high energy planetary mill with agate jar and balls. The processing variables to evaluate their effect on the mixture homogeneity, microstructure, and electrical properties were milling speed (100, 300, and 600 rpm) and time (20, 60, and 180 min). The aim of this study was to find the milling parameters that produce the best homogeneity of dopants within the mixture and to relate those parameters with the repeatability of electrical properties of as prepared samples. The ceramic samples exhibit a non-linear dependence of current-voltage and may be considered as varistors. Best results for repeatability of electrical properties were achieved when the ceramic system is milled for 60 min at 300 rpm. It was found that the way dopants are distributed within the ceramic system is dependent on milling conditions.